Transport Provision of Evacuation - Tomek, Miroslav; Seidl, Miloslav; Rostekova, Lenka (Communications - Scientific letters of the University of Zilina, 2002)
Risks of every person’s life and property endangerment caused by natural disaster, technological average or social crisis are increasing. It is the reality of life that this danger can arise whenever and wherever, often even in unexpected situations. One of the most important tasks when solving any special situation is salvage of persons, animals and property from endangered buildings or areas. Evacuation provision and its actual realization are inseparable parts of this activity. This article deals with evacuation provision and solves its technical provision with a focus on logistic provision.